Coaching unemployed managers and professionals through the trauma of unemployment: Derailed or undaunted?*. Issue 3 (July 2015) - Gray, David E; Gabriel, Yiannis; Goregaokar, Harshita
The economic crisis of 2008/2009 has increased unemployment among managers, particularly older managers, a group under-researched empirically. This longitudinal study assesses the efficacy of executive coaching for a group of unemployed professionals who participated in an intensive coaching programme aimed at reintegrating them into the economy. Results suggest that the majority were positive about coaching, a process that helped them to reflect on and learn from their new circumstances. Findings also contradict other studies, indicating cautious, cool and even hostile responses to coaching. The study highlights the mental fragility of previously successful, now unemployed managers. From a policy perspective, interventions should start earlier (before employees leave an organisation) and finish later. From a social science perspective, executive coaching represents a modest but sometimes effective initiative to help unemployed professionals to re-write their life stories to make sense of their experiences.